Rehabilitation of kimberlite tailings in the afro‐alpine zone of Lesotho: seed germination and plant performance of native grassland species across different topsoil mixtures. Issue 3 (6th September 2021) - Ntloko, Bongani R.; Siebert, Stefan J.; Mokotjomela, Thabiso M.
Abstract : Environmental rehabilitation is mandatory for mining operations in many countries, including Lesotho. At Letšeng Diamond Mine in Lesotho, waste residues of kimberlite tailings create a hostile environment for the establishment of plant species during vegetation restoration. In this study, we investigated seed germination of native grassland species and tested the best performing species on different topsoil mixtures with kimberlite tailings in the Afro‐alpine zone in Lesotho. Rapid germination tests showed highly significant differences in the number of seedlings that emerged for different plant species: the grass Tenaxia disticha (% mean ± SE: 80 ± 17%; n  = 36) and the forb Hesperantha schelpeana (56 ± 14%) were highest but nonsignificantly different to each other, while other species were significantly lower and nonsignificantly different to each other. In all treatments, seed germination of T. disticha was significantly higher than the experimental control, while the treatments that were covered with topsoil did not differ significantly. In addition, T. disticha seedling height and basal width varied significantly over time with seedlings in all the treatments growing significantly taller than those in the experimental control. Also, seedling basal width showed significant increase during the third growing season while height remained constant. We concluded that kimberlite tailings ameliorated with topsoil encourage plant establishment and performance of T. disticha, and this medium could be used to stabilize disturbed mine landscapes in the Afro‐alpine zone of Lesotho.